Involvement of RAGE and Oxidative Stress in Inflammatory and Infectious Skin Diseases - Fabrizio Guarneri; Paolo Custurone; Valeria Papaianni; Sebastiano Gangemi (MDPI AG, 2021)
The surface receptor for advanced glycosylation end-products (RAGE) and its soluble (sRAGE) and endogenous secretory (EN-RAGE) forms belong to the superfamily of toll-like receptors and play important roles in inflammation and autoimmunity, directly or through binding with advanced glycosylation end-products (AGE) and advanced oxidation protein products (AOPP). We reviewed the literature on the role of RAGE in skin diseases. Research in this field is still rather limited (28 articles) but suggests the involvement of RAGE and RAGE-related pathways in chronic inflammatory diseases (lupus, psoriasis, atopic dermatitis, and lichen planus), infectious diseases (leprosy, Staphylococcus aureus-induced skin lesions), alterations of the repairing processes in diabetic skin, systemic sclerosis, and ulcers. These data prompt further research in this field, which not only will be useful to better understand the pathogenetic mechanisms of diseases, but is also likely to have intriguing clinical implications. Indeed, when their role in the complex and multifactorial inflammatory balance will be adequately defined, RAGE and related molecules could be used as markers of disease severity and/or response to treatment. Moreover, future promising therapeutic perspectives could be topical administration of some of these molecules (e.g., sRAGE) to modulate local inflammatory response and/or the development of anti-RAGE antibodies for systemic treatment.